2000
DOI: 10.1002/1097-0347(200009)22:6<591::aid-hed8>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between genetic susceptibility to head and neck cancer with the expression of common fragile sites

Abstract: Background Numerous studies have recently been conducted to investigate genetic mechanisms in cancer causes and pathogenesis. Some of these studies have shown that there were certain specific chromosomal defects in normal cells of cancer patients and in their first‐degree relatives. It was suggested that these individuals were susceptible to cancer development when compared with people without these defects. Materials and Methods Chromosomal anomalies, such as gaps, breaks, and acentric fragments, and fragile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…In addition to this correlation, breast and cervical cancer patients showed a significantly higher expression of fragile sites when treated with aphidicolin than did control groups 49. Similar results were obtained by many others 35,50–53…”
Section: Common Fragile Sites and Cancersupporting
confidence: 85%
See 1 more Smart Citation
“…In addition to this correlation, breast and cervical cancer patients showed a significantly higher expression of fragile sites when treated with aphidicolin than did control groups 49. Similar results were obtained by many others 35,50–53…”
Section: Common Fragile Sites and Cancersupporting
confidence: 85%
“…49 Similar results were obtained by many others. 35,[50][51][52][53] In many cases, fragile sites have been suspected as regions harboring tumor suppressor genes (TABLE 2). The most popular example is FHIT (fragile histidine triad), a gene in the telomeric region of FRA3B.…”
Section: Common Fragile Sites and Cancermentioning
confidence: 99%
“…3,4 However, genetic susceptibility may also modulate the risk of SCCHN because only a fraction of individuals who smoke or drink develop this disease. 5,6 Recent molecular epidemiological studies have demonstrated that polymorphisms in DNA repair genes contribute to genetic susceptibility to SCCHN. 7,8 Therefore, studies of biological relevance of newly identified genetic polymorphisms 9 should ultimately help identify those at high risk for carcinogenesis and eventually improve cancer prevention and chemoprevention programs.…”
mentioning
confidence: 99%
“…Activation of common fragile sites by aphidicolin was detected in lymphocytes from colon, rectum, head and neck cancer patients and in their first-degree relatives, with a significant difference compared to lymphocytes of normal controls (Egeli et al, 2000;Tunca et al, 2000a,b). Moreover, several tumor suppressor genes have been cloned from regions containing fragile sites: FHIT from FRA3B (Huebner et al, 1998), TESTIN from FRA7G (Tatarelli et al, 2000) and FOR from FRA16D .…”
Section: Involvement Of Fra6f In Senescence Oncogenesis and Schizophmentioning
confidence: 99%